On application of X-ray aproximation method for studying the substructure of sufficiently perfect samples - Malykhin, S.V.; Garkusha, I.E.; Makhlay, V.A.; Surovitsky, S.V.; Reshetnyak, M.V.; Borisova, S.S. (Functional Materials, 2017)
The technique of X-ray diffraction investigation of coherence length and micro-strain level using approximation of diffraction line profiles by Gaussian and Cauchy functions as well as by harmonic analysis has been worked out for tungsten samples with quite perfect structure. The importance of right choice of a standard for obtaining the reasonable measurement results has been demonstrated. For the first approximation the possibility to use the spectral line width for calculation of the reflection true (physical) broadening has been shown. The contributions of basic instrumental factors into the reflection geometric broadening were estimated.